Computational investigations of physicochemical, pharmacokinetic, toxicological properties and molecular docking of betulinic acid, a constituent of Corypha taliera (Roxb.) with Phospholipase A2 (PLA2) - Mohammad Firoz Khan; Nusrat Nahar; Ridwan Bin Rashid; Akhtaruzzaman Chowdhury; Mohammad A. Rashid (BMC, 2018)
Abstract Background Betulinic acid (BA) is a natural triterpenoid compound and exhibits a wide range of biological and medicinal properties including anti-inflammatory activity. Therefore, this theoretical investigation is performed to evaluate (a) physicochemical properties such as acid dissociation constant (pKa), distribution coefficient (logD), partition coefficient (logP), aqueous solubility (logS), solvation free energy, dipole moment, polarizability, hyperpolarizability and different reactivity descriptors, (b) pharmacokinetic properties like human intestinal absorption (HIA), cellular permeability, skin permeability (PSkin), plasma protein binding (PPB), penetration of the blood brain barrier (BBB), (c) toxicological properties including mutagenicity, carcinogenicity, risk of inhibition of hERG gene and (d) molecular mechanism of anti-inflammatory action which will aid the development of analytical method and the synthesis of BA derivatives. Methods The physicochemical properties were calculated using MarvinSketch 15.6.29 and Gaussian 09 software package. The pharmacokinetic and toxicological properties were calculated on online server PreADMET. Further, the molecular docking study was conducted on AutoDock vina in PyRx 0.8. Results The aqueous solubility increased with increasing pH due to the ionization of BA leading to decrease in distribution coefficient. The solvation energies in water, dimethyl sulfoxide (DMSO), acetonitrile, n-octanol, chloroform and carbon tetrachloride were − 41.74 kJ/mol, − 53.80 kJ/mol, − 66.27 kJ/mol, − 69.64 kJ/mol, − 65.96 kJ/mol and − 60.13 kJ/mol, respectively. From the results of polarizability and softness, it was clear that BA is less stable and hence, kinetically more reactive in water. BA demonstrated good human intestinal absorption (HIA) and moderate cellular permeability. Further, BA also exhibited positive CNS activity due to high permeability through BBB. The toxicological study revealed that BA was a mutagenic compound but noncarcinogenic in mice model. Moreover, molecular docking study of BA with PLA2 revealed that BA interacts with GLY22 & GLY29 through hydrogen bond formation and LEU2, PHE5, HIS6, ALA17, ALA18, HIS47 and TYR51 through different types of hydrophobic interactions. The binding affinity of BA was − 41.00 kJ/mol which is comparable to the binding affinity of potent inhibitor 6-Phenyl-4(R)-(7-Phenyl-heptanoylamino)-hexanoic acid (BR4) (− 33.89 kJ/mol). Conclusions Our computed properties may assist the development of analytical method to assay BA or to develop BA derivatives with better pharmacokinetic and toxicological profile.